1996
DOI: 10.1111/j.1432-1033.1996.0056t.x
|View full text |Cite
|
Sign up to set email alerts
|

Oncostatin M Differentially Regulates Tissue Inhibitors of Metalloproteinases TIMP‐1 and TIMP‐3 Gene Expression in Human Synovial Lining Cells

Abstract: Tissue inhibitor of metalloproteinases (TIMP) 1, 2 and 3 are related proteins that can form complexes with all known matrix metalloproteinases (MMPs). They inhibit the action of MMPs on extracellular matrix components. The balance of MMPs and TlMPs is important for tissue remodeling and its disturbance is believed to play a crucial role in pathophysiological processes such as tumor metastasis, destruction of cartilage and fibrosis. Cytokines and growth factors were found to regulate TIMPs and MMPs in a complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
0
3

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 53 publications
4
37
0
3
Order By: Relevance
“…So far, most studies corroborating the involvement of OSM in the development and progression of RA have highlighted its contribution to cartilage breakdown preferentially by up-regulation of MMPs and aggrecanases (18,20,22,26,46) as well as changes in the MMP:TIMP ratio in favor of MMPs (19,37). In this study, we identified OSM as the main regulator of CCL13 chemokine expression by SFs.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…So far, most studies corroborating the involvement of OSM in the development and progression of RA have highlighted its contribution to cartilage breakdown preferentially by up-regulation of MMPs and aggrecanases (18,20,22,26,46) as well as changes in the MMP:TIMP ratio in favor of MMPs (19,37). In this study, we identified OSM as the main regulator of CCL13 chemokine expression by SFs.…”
Section: Discussionsupporting
confidence: 52%
“…Neutrophils, normal dermal fibroblasts, and RASFs were generated as described previously (33)(34)(35). Lung fibroblasts were kindly provided by P. Marynen (University of Leuven, Leuven, Belgium [36]), and the normal SFs and normal cervical fibroblasts were provided by E. Van de Leur (RWTH Aachen University Hospital, Aachen, Germany [37,38]). Primary human monocytes were isolated from fresh blood using the Dynal Monocyte Negative Isolation Kit as described by the manufacturer (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…Production of TIMP2 in dermal fibroblasts at the mRNA and protein levels was shown to be stimulated by IL-4, but not by TGF-ß1 (112). TGF-ß1 has been shown to induce expression of both TIMP1 and TIMP3 in human synovial lining cells (113). Moreover, increased expression of TIMP3, under influence of TGF-ß1, has been observed in fibroblasts (114).…”
Section: Discussionmentioning
confidence: 99%
“…However, it also induces the growth of AIDS-associated Kaposi's sarcoma cells (15,16). Because of its ability to induce TIMP-1 and TIMP-3, pro-fibrotic properties have also been attributed to OSM (17)(18)(19). Indeed, transgenic mice expressing OSM in islet ␤-cells develop severe fibrosis (20).…”
mentioning
confidence: 99%